2010
DOI: 10.1016/j.expneurol.2010.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Descending brain neurons in larval lamprey: Spinal projection patterns and initiation of locomotion

Abstract: In larval lamprey, partial lesions were made in the rostral spinal cord to determine which spinal tracts are important for descending activation of locomotion and to identify descending brain neurons that project in these tracts. In whole animals and in vitro brain/spinal cord preparations, brain-initiated spinal locomotor activity was present when the lateral or intermediate spinal tracts were spared but usually was abolished when the medial tracts were spared. We previously showed that descending brain neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 82 publications
(167 reference statements)
0
25
0
Order By: Relevance
“…The number of processes in the dorsomedial region is recovered at 2 wpl both rostral and caudal to the site of injury. Most of the processes of the lateral region correspond to small RS glutamatergic neurons of several rhombencephalic nuclei (anterior, middle and posterior rhombencephalic reticular nuclei41 and the postero-lateral vagal group42) and to processes of the cells of the lateral population of the spinal cord. Based on the know timing of regeneration of descending neurons (see above), the recovery of the number of processes at 2 wpl in the caudal stump has to be attributed to the intrinsic lateral spinal neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of processes in the dorsomedial region is recovered at 2 wpl both rostral and caudal to the site of injury. Most of the processes of the lateral region correspond to small RS glutamatergic neurons of several rhombencephalic nuclei (anterior, middle and posterior rhombencephalic reticular nuclei41 and the postero-lateral vagal group42) and to processes of the cells of the lateral population of the spinal cord. Based on the know timing of regeneration of descending neurons (see above), the recovery of the number of processes at 2 wpl in the caudal stump has to be attributed to the intrinsic lateral spinal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Processes of the dorsomedial region comprise the dorsal column (DC) (constituted by axons of the primary sensory dorsal cells and dorsal root ganglion cells4344) as well as the descending trigeminal tract, which is located next to the DC45, and processes of the cells of the dorsal population. In addition, some descending axons from the mesencephalic reticular nucleus (MRN) and the antero-lateral vagal group (ALV), which project to the medial (dorsal and/or ventral) spinal region42, may also descend in this region. Axons of the dorsal cells have been shown to have bad regenerative capacity14 and previous studies have shown that the projections from the ALV do not recover to normal levels even at 32 wpl, whereas axons of the MRN show good recovery at 32 wpl16.…”
Section: Discussionmentioning
confidence: 99%
“…Inputs from these regions converge on reticulospinal neurons, which in turn activate spinal networks (El Manira et al, 1997;Dubuc et al, 2008;Shaw et al, 2010). However, in all these cases, the expression of locomotor activity required that these centers are stimulated continuously and the activity declined rapidly upon termination of the stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the RS neurons that initiate locomotion project their descending axons primarily in the lateral parts of the spinal cord (McClellan, 1988; Shaw et al, 2010). In larval lamprey, DLM- or VMD-initiated locomotor activity usually is abolished or significantly attenuated when neural activity is blocked in reticular nuclei (Paggett et al, 2004), and RS neurons receive direct synaptic inputs from the VMD and DLM locomotor areas (El Manira et al, 1997; Paggett et al, 2004).…”
Section: Introductionmentioning
confidence: 99%